Stability of anti-HIV antibodies in serum samples stored for two to eighteen years periods - Marcia Jorge Castejon; Rosemeire Yamashiro; Camila Cardoso de Oliveira; Carmem Aparecida de Freitas Oliveira; Mirthes Ueda (Sociedade Brasileira de Patologia Clínica, 2014)
Introduction: The antibodies have an important role in the serodiagnosis, constituting the most widely used biomarkers to detect and confirm various diseases. Objective: To investigate the reproducibility of anti-human immunodeficiency virus (HIV) antibodies reactivity, to assess the stability of the sera samples stored at -20ºC for two to eighteen years. Method: Sera were collected in the period 1988-2004 for routine anti-HIV antibodies diagnostic testing. The remaining samples stored at -20ºC, were analyzed in this study. Serum sample stability was assessed by enzyme-linked immunosorbent assay/enzyme immunoassay (ELISA/EIA), indirect immunofluorescence assay (IFA), and Western blot (WB) for detecting anti-HIV antibodies. The previously found results (1988-2004) and those obtained in 2006 were subjected to Kappa index analysis. Result: In the period 1988-to 2004, the degree of concordance of the ELISA/EIA, IFA and WB results were considered, good (k = 0.80), regular (k = 0.35), and good (k = 0.63), respectively. Conclusion: Regarding HIV serologic test, the serum samples were stable for 18 years in ELISA/EIA and for 4 years in IFA technique, however, for the WB methodology it was not possible to determine the time of stability of the anti-HIV antibodies.